Epidemiological profile of syphilis cases in pregnant in a public maternity - Deusiane Pereira da Silva; Karla Joelma Bezerra Cunha; Camila Marinho Lages; Ana Carolina Dias Albuquerque; Vagner Ferreira dos Santos; Lívia Carvalho Pereira (Universidad de Alicante, 2019)
Objective: The objective of the study was to analyze the epidemiological profile of syphilis cases in pregnant women in a maternity hospital from Teresina, Piauí, in 2016. Method: Descriptive and documental epidemiological research with quantitative approach, carried out at the Epidemiological Surveillance Service of the maternity, from November 2016 to January 2017, based on data from the Notification of Injury Information System (SINANNET). Data were stratified according to age group, education, gestational age in diagnosis, titration of the non-treponemic test, syphilis classification and partner adherence. Results and discussion: In relation to the prevalence, seventy-five cases were notified in 2016, corresponding to 2,8%. The disease was prevalent in women aged from 20 to 29 years old who had incomplete elementary school education. The majority (77,33%) were diagnosed in third trimester, 22,7% of the pregnant women presented VDRL of 1:16, the most frequent clinical classification was tertiary and latent with 61,33% of the cases, with regard to the partners' adherence, only 32% performed the treatment. Conclusions: It's necessary a rigorous diagnosis, treatment and follow-up in the attempt to reduce cases of syphilis in pregnant women and congenital syphilis, as well as to break the chain of transmission with directed strategies and actions in the fight against the disease.